Elements regulating an alternatively spliced exon of the rat fibronectin gene. - Huh, G S (1993)
We have investigated the regulation of splicing of one of the alternatively spliced exons in the rat fibronectin gene, the EIIIB exon. This 273-nucleotide exon is excluded by some cells and included to various degrees by others. We find that EIIIB is intrinsically poorly spliced and that both its exon sequences and its splice sites contribute to its poor recognition. Therefore, cells which recognize the EIIIB exon must have mechanisms for improving its splicing. Furthermore, in order for EIIB to be regulated, a balance must exist between the EIIIB splice sites and those of its flanking exons. Although the intron upstream of EIIIB does not appear to play a role in the recognition of EIIIB for splicing, the intron downstream contains sequence elements which can promote EIIIB recognition in a cell-type-specific fashion. These elements are located an unusually long distance from the exon that they regulate, more than 518 nucleotides downstream from EIIIB, and may represent a novel mode of exon regulation.